2019
DOI: 10.22320/07190700.2019.09.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de impacto ambiental mediante la introducción de indicadores a un modelo BIM de vivienda social

Abstract: Building Information Modeling (BIM) constituye una herramienta versátil para analizar el ciclo de vida de los edificios y el uso eficiente de los recursos, reducción, reuso y reciclado de residuos de construcción y demolición hacia un parque edilicio sin carbono para 2020 en Europa. Este trabajo propone una nueva metodología para incorporar indicadores: energía incorporada, emisiones de CO2, residuos de construcción y demolición además de sólidos urbanos, en modelos BIM que evalúan el impacto ambiental siguien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
(6 reference statements)
0
8
0
1
Order By: Relevance
“…Lützkendorf et al [85] found that BIM could determine the amount of materials and cost estimation, which can be helpful for the environmental assessment. Mercader-Moyano et al [89] applied a different strategy by combining costs with the environmental assessment using BIM to define the composition of work units in the case of a reinforced concrete structure. The amount and section of the reinforcement bars was then represented in the BIM elements, and their environmental assessment was calculated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lützkendorf et al [85] found that BIM could determine the amount of materials and cost estimation, which can be helpful for the environmental assessment. Mercader-Moyano et al [89] applied a different strategy by combining costs with the environmental assessment using BIM to define the composition of work units in the case of a reinforced concrete structure. The amount and section of the reinforcement bars was then represented in the BIM elements, and their environmental assessment was calculated.…”
Section: Discussionmentioning
confidence: 99%
“…This was already done by Abanda et al [86], who developed a specific application to link BIM models with the New Measurement Rules (NMR) in the UK standard for public procurement [87] by using the Bath Inventory of Carbon and Energy (Bath ICE) [88]. Also, Mercader-Moyano et al [89] applied an environmental impact assessment to a BIM environment by using a construction cost database for the quantity take-off.…”
Section: Reliabilitymentioning
confidence: 99%
“…Following these premises, the different scenarios are justified, the origin of the data, their traceability are defined, and the calculation method to be used is recognized. The different aggregated data for embodied carbon will be integrated into a quantification model through shared parameters (In Building Information Modeling), in line with what was proposed by Mercader Moyano for the determination of the EE (Embodied Energy) of the existing construction solutions in social housing [51]. Subsequently, the results obtained through the said tool will be analyzed from an LCA perspective.…”
Section: Methodological Basis For the Selection And Calculation Of Enmentioning
confidence: 99%
“…The BIM methodology was used with the LCC of sustainable building components. Mercader et al (2019) analyzed a set of dwellings in Spain built in reinforced concrete, including indicators of embodied energy, CO 2 emissions, construction waste, demolition, urban solid waste, and construction costs. Software REVIT, Presto, Medit, and the Andalusian Construction Cost Base (ACCD) integrated with BIM methodology.…”
Section: Technology Resources In the Assessment Of Building Life Cyclementioning
confidence: 99%